Urban foraging : find, gather, and cook 50 wild plants - Rose, Lisa M. (Herbalist) (Timber Press, 2022)
"We can all make tasty and surprising dishes from wild food found in our cities. With expert advice from professional forager and bestselling Timber author Lisa Rose, alongside elegant photography, this handy guide explains how to identify and where to find 50 plants that grow across the temperate US; accompanying simple recipes help prepare wild feasts"--